2021
DOI: 10.3390/biom11091279
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polymorphisms in Collagen-Encoding Genes in Intervertebral Disc Degeneration

Abstract: (1) Background: The purpose of this review is to analyze domestic and foreign studies on the role of collagen-encoding genes polymorphism in the development of intervertebral discs (IVDs) degeneration in humans. (2) Methods: We have carried out a search for full-text articles published in e-Library, PubMed, Oxford Press, Clinical Case, Springer, Elsevier and Google Scholar databases. The search was carried out using keywords and their combinations. The search depth was 5 years (2016–2021). In addition, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Moreover, it showed that several dysregulated genes played important roles in the PPI network, including genes that were related to cytokines (IL6, SOCS3, CXCL2, CXCL1, and TLR2), complements (ITGAM), ECM composition including the collagen family, and aggrecan (COL3A1, COL2A1, COL9A2, COL9A3, COL4A1, COL8A2, ACAN, and COMP), as well as cell proliferation or differentiation transcription factors (FOS and FOXO1). In previous studies, collagen and aggrecan turnover in ECM was observed in degenerated discs (Sivan et al, 2014;Trefilova et al, 2021). COMP, the cartilage oligomeric matrix protein, was also found as a marker of IVDD (Qi et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, it showed that several dysregulated genes played important roles in the PPI network, including genes that were related to cytokines (IL6, SOCS3, CXCL2, CXCL1, and TLR2), complements (ITGAM), ECM composition including the collagen family, and aggrecan (COL3A1, COL2A1, COL9A2, COL9A3, COL4A1, COL8A2, ACAN, and COMP), as well as cell proliferation or differentiation transcription factors (FOS and FOXO1). In previous studies, collagen and aggrecan turnover in ECM was observed in degenerated discs (Sivan et al, 2014;Trefilova et al, 2021). COMP, the cartilage oligomeric matrix protein, was also found as a marker of IVDD (Qi et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…The extracellular matrix of IVD is composed mainly of collagen, with type I collagen representing the primary constituent of the annulus fibrosus ( Yang et al, 2020 ) and type II collagen serving as the main component secreted by nucleus pulposus cells ( Fernandes et al, 2020 ). Correlative research demonstrated an association between collagen gene polymorphisms and IVD deterioration ( Trefilova et al, 2021 ). Polymorphisms in COL1A1 Sp1 and COL11A1 C4603T are associated with IDD risk, and these collagen genes may be used to treat or prevent IDD ( Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a high SERPINA1 expression in NPD, C5 performed well in the ANGPTL signaling network. Collagen is a part of NP, and its dysfunction occurs with IVD degeneration ( Trefilova et al, 2021 ). C1 and C3 had higher SERPINA1 expressions in NPH, and their communications in COLLAGEN signaling network exhibited higher strength.…”
Section: Discussionmentioning
confidence: 99%
“…The classic twin experiment confirmed the genetic correlation of IVDD and LBP to some extent ( Battié et al, 1995 ; Battié et al, 2007 ). Moreover, genetic polymorphism studies may also provide a basis for this, as genetic polymorphisms in inflammatory factors (IL-1α/β, IL-6, and TNF-α), MMPs (MMP-1, -2, -3), collagen (COL), aggrecan (ACAN), and cartilage intermediate proteins may be associated with the pathogenesis of IVDD in populations from several countries ( Mayer et al, 2013 ; Harshitha et al, 2018 ; Trefilova et al, 2021 ). It is well known that both prolonged compression, strain, and acute nonphysiological loading acting on the IVD can lead to a range of changes, such as tissue damage, reduced vascular buds, decreased cellular activity, inflammatory factor release, and ECM degradation ( Alkhatib et al, 2014 ; Zhan et al, 2020 ; Zhan et al, 2021 ; Zhou et al, 2021 ), which ultimately result in IVDD.…”
Section: Mechanisms and Treatment Strategies Of Ivddmentioning
confidence: 99%